Proactive Personality and Innovative Work Behavior: Through the Juxtapose of Schumpeter's Theory of Innovation and Broaden-And-Build Theory - Li, Weizheng; Gill, Shabeeb Ahmad; Wang, Yang; Safdar, Muhammad Adeel; Sheikh, Muhammad Ramzan (Frontiers in Psychology, 2022)
This study aimed to unfold the implicit interplay of open innovation (OI) and perceived insider status (PIS) between the relationship of proactive personality (PP) and innovative work behavior (IWB). The phenomenon studied the moderated mediation of OI and PIS through the combined optic of the theory of innovation and the broaden-and-build theory. The nature of this study was post-positivist. The two-step approach of structural equation modeling was implemented. First, quantitative data was collected through an online questionnaire from the employees of IT industries in China. The study sample consisted of 460 responses used for data analysis in SPSS and AMOS version 26. This study was based on mediated moderation which was statistically similar to model 15 of process macro. There were six hypotheses based on the theoretical framework. The result of H6 was rejected, which demonstrated that the conditional direct effect of OI and PIS mediated moderation on PP and IWB. The results comprehensively testified to the theoretical framework.